Interaction of the Oncofetal Thomsen–Friedenreich Antigen with Galectins in Cancer Progression and Metastasis - Sindrewicz, Paulina; Lian, Lu-Yun; Yu, Lu-Gang (Frontiers in Oncology, 2016)
Aberrant glycosylation of cell membrane proteins is a universal feature of cancer cells. One of the most common glycosylation changes in epithelial cancer is the increased occurrence of the oncofetal Thomsen-Friedenreich disaccharide Galβ1-3GalNAc (T or TF antigen), which appears in about 90% of cancers but is rarely seen in normal epithelium. Over the past few years, increasing evidence has revealed that the increased appearance of TF antigen on cancer cell surface plays an active role in promoting cancer progression and metastasis by interaction with the β-galactoside-binding proteins, galectins, which themselves are also frequently overexpressed in cancer and pre-cancerous conditions. This review summarizes the current understanding of the molecular mechanism of the increased TF occurrence in cancer, the structural nature and biological impact of TF interaction with galectins, in particular galectin-1 and -3, on cancer progression and metastasis.